The Nexus Between Islamic Finance, Trade Openness, FDI, Economic Growth and Carbon Emission: Panel Data Analysis in Islamic Countries - Romadhon, Roval; Zulaikha, Siti (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study aims to analyze the impact of economic growth, Islamic finance, trade openness, FDI, and urbanization on carbon emissions in member countries of the Organization of Islamic Cooperation (OIC). GDP per capita serves as the indicator for economic growth, while Islamic financial assets represent Islamic finance. The study employs panel data regression analysis using the fixed effect model, identified as the best model based on the Hausman test, with data processed and analyzed through EViews 13. The results indicate a significant negative impact of economic growth on carbon emissions in high-income OIC countries, whereas in middle-income countries, economic growth has a significant positive effect on carbon emissions, partially. Simultaneously, economic growth, Islamic finance, trade openness, FDI, and urbanization collectively have a positive influence on carbon emissions in OIC member countries during the 2013–2022 period. These results can serve as a reference for governments, institutions, and organizations in formulating policies or regulations to enhance sustainable economic stability and environmental quality within the OIC member countries.